A CRITICAL DISCOURSE ANALYSIS OF ONLINE MEDIA NEWS OF OMNIBUS LAW CONTENT IN KOMPAS.COM - Kartika Sari, Yuni; Pradipta, Bramantya (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2021)
The main purpose of this research is to complete one of the requirements for completing the study. The study is going to present about Critical Discourse Analysis in online media of Omnibus Law content, in addition, this research aims to reveal ideology in a discourse. The results of this study are expected to be useful in the understanding the term of CDA. This study aim is to reveal the ideology that implied in online news about controversial articles in the content of Omnibus Law in kompas.com and The study include its’ textual context, social cognition and social context to analyze the ideology contained therein. This research is conducted using qualitative research method that is entirely based on the novel and various supporting sources such as journals, articles, or websites.